Assessing the impacts of drought on net primary productivity of global land biomes in different climate zones. (November 2021) - Liu, Yangyang; Zhou, Ronglei; Wen, Zhongming; Khalifa, Muhammad; Zheng, Cheng; Ren, Hanyu; Zhang, Zhaoying; Wang, Zhenqian
Highlights: Response of vegetation to drought varies greatly in different climatic regions. The effect of drought on vegetation in humid areas is lower than that in dry area. Water balance plays a key role in affecting the response of vegetation to drought. The sensitivity of different vegetation to drought is quite different. Abstract: Drought is the most widespread event under climate change and is projected to lead to high uncertainties in quantifying the terrestrial carbon exchange. However, considering the complexity of drought quantification and the differences in the physiological responses to drought among different vegetation types, the potential mechanisms of vegetation in response to drought across different climate regions and their responses to drought at varying time scales remain unclear globally. Here, we analyzed the response of vegetation activity to drought at different time scales and determined the time scale dominating the drought-induced vegetation variations, then explored its potential driving factors (temperature, precipitation, potential evapotranspiration, and water balance) under different climatic conditions and vegetation types from 2000 to 2015 using the Standardized Precipitation Evapotranspiration Index (SPEI) and Net Primary Productivity (NPP). Our results indicated that the NPP-SPEI correlation was stronger under arid and semi-arid conditions compared to that in humid and sub-humid zones globally. Vegetation mainly responded to the drought from short to medium time scales and the shortest response time scale was observed for deciduous needle-leaf forests and closed shrublands, which mainly located in semi-arid regions of southeastern Australia, central Africa, and southern Russia. Moreover, grassland and cropland ecosystems were found to be also highly vulnerable to drought across the globe. Analysis of the effects of various meteorological factors on NPP-SPEI correlation and drought timescales showed that water balance was the most predominant factor affecting the response of vegetation to drought. In particular, the increase in water balance significantly reduced the response intensity of vegetation to drought and prolonged the response timescales. Analysis of the effects of various meteorological factors on NPP-SPEI correlation and drought time-scales showed that water balance was the most predominant factor affecting the response of vegetation to drought. In particular, the increase in water balance significantly reduces the response intensity of vegetation to drought and prolongs the response time-scales. Therefore, the identification of the dominant timescales at which drought mostly impact land biomes is projected to assist assessing the stability of terrestrial ecosystem and thus support drought mitigation to reduce land degradation.